Engineering Graduates' Skill Acquisition and Employers Skill Need as applied to Science Education in Ethiopia - Teshome, Asmera; Oumar, Jeilu (Universitas Terbuka, 2023)
Demand for relevant skills and competences have increased with changing science and technology, globalization, and the intensity and complexity of the business environment across the world. This study investigated levels of engineering graduate skill acquisition and employers' skill needs as applied to science education. Using a mixed-methods approach, the study employed both primary and secondary sources of data. The study involved 275 participants recruited using simple random and purposive sampling techniques. Data were analyzed using the mean, standard deviation, and one-way ANOVA. The study found a wider mismatch between levels of higher education supply and labor market needs for indicators of academic, technical, interpersonal, and generic skills. While higher education moderately equipped engineering graduates with the majority of indicators of these skill sets, labor market needs for the same skills remain high. The mismatches between the demand and supply of skills have several implications, it compromises firms' productivity, result in market losses, hamper economic growth, competitiveness, and innovative capacity at the macro-economic level, decrease quality human capital by discouraging investment in education and training, and challenge graduates in finding jobs suitable for their field of study. These require universities and employers to conduct real labor market skills' needs assessments before designing training curriculum; shifting curriculum delivery from theory-focused to practical-oriented modes of teaching and ensuring learners' acquisition of skills demanded by employers; and establishing strong and sustainable linkages between industries and training institutes. It is also good if future research focuses on skills employees acquire at work through experience and factors attributed to mismatches between higher education skill supply and employers' skill needs.